Adjusting to changing environments: virtual preseason SCAT5 assessment in Canadian male youth football players - Syrydiuk, R. A.; Penner, L. C.; Sick, S.; Eliason, P.; Galarneau, J.-M.; Leggett, B.; Galea, O.; Schneider, K. J.; Emery, C. A. (Clinical Journal of Sport Medicine, 2023)
Objective: To provide preseason reference scores for Canadian youth tackle football players on the Sport Concussion Assessment Tool 5 (SCAT5) and to examine whether age, concussion history, and self-reported medical diagnoses are associated with SCAT5 subcomponent performance.